Retinopathy in Pregnancy Induced Hypertension - Saira Bano, Ali Raza, Muhammad Imran Janjua (Pakistan Journal of Ophthalmology, 2015)
Purpose: The purpose of this study was to observe the prevalence of Hypertensive Retinopathy in patients with Pregnancy Induced Hypertension. Materials and Methods: This cross-sectional study was carried out at Holy Family Hospital, Rawalpindi from July 2013 to July 2015. 168 patients with Pregnancy Induced Hypertension were examined for any fundus changes. Patient’s age, number of pregnancies, gestation period, blood pressure and proteinuria were noted. Pupils were dilated and fundus examination was done by direct ophthalmoscope. The data was analyzed by SPSS program. Results: A total of 168 patients were examined, 42 (25%) were primi-gravida, 91 (54.2%) were multi-gravida and 35 (20.8%) were grand multi-gravida. The mean age was 27.66 (± 5.20) years. The average gestation period was 33.36 (±3.91) weeks. 126 (75%) patients had gestational hypertension, 37 (22%) had preeclampsia and 5 (3%) patients had eclampsia. Hypertensive retinopathy was observed in 87 (51.78%) patients. Central serous chorioretinopathy (CSCR) was seen in 3 (1.8%) patients. A statistically significant positive correlation was seen between the severity of retinal hypertensive changes and blood pressure (p = 0.005), the grade of proteinurea (p = 0.000), severity of disease (p = 0.000) and no of pregnancies (p = 0.001). Conclusion: The level of blood pressure, severity of disease and proteinuria are significantly related with severity of hypertensive retinopathy in cases of PIH. Retinal examination can greatly help in predicting the severity of PIH and also in timely diagnosis and management of such cases. Key Words: Retinopathy, hypertension, pregnancy.